Analisis Quality of Service (QoS) pada Jaringan PC dan Perangkat Bergerak pada Sistem Smart Door Lock Berbasis Internet of Things - Muhammad Nazhrun Nabil (Institute of Information Technology and Social Science (IITSS), 2021)
The development of Internet of Things (IoT) technology has encouraged the use of computer networks in security systems, including smart door locks. Network performance is an important factor because it affects system reliability. This study aims to analyze the Quality of Service (QoS) of PC and mobile device networks in an IoT-based smart door lock system using the Wireshark application. The QoS parameters analyzed include delay, packet loss, throughput, and jitter based on the TIPHON standard. The research method used was action research, consisting of the stages of diagnosis, planning, action, and evaluation. The measurement results showed that the delay parameter was in the good to very good category, jitter was in the moderate to good category, packet loss was still dominated by the poor category especially during off-peak hours and throughput ranged from very good to poor depending on network traffic conditions. Based on these findings, it can be concluded that the network quality in the smart door lock system was generally adequate, but improvements are still needed in packet loss and data traffic stability.